Mathematical analysis of the generalized Benjamin and Burger-Kdv equations via the extended trial equation method - Belgacem, Fethi Bin Muhammad; Bulut, Hasan; Baskonus, Haci Mehmet; Akturk, Tolga (University of Bahrain, 2014)
In this paper, using the Extended Trial Equation (ETEM), we get new traveling wave solutions of the Generalized Benjamin, the Generalized Burger-Kdv Equations (GBE, GBKE). The obtained solutions not only constitute a novel analytical viewpoint in nonlinear complex phenomena, but they also form a new stand alone basis from which physical applications in this arena can be comprehended further, and moreover investigated. Furthermore, to concretely enrich this research production, we provide illustrative, Mathematica Release 7 based, 3D graphics of the gotten solutions, with well chosen, yet structure revealing parameters. © 2013 .
Keywords: Extended trial equation method; Generalized benjamin equation; Generalized burger-kdv equation